Model Intervensi Kolaboratif Orang Tua–Guru Dalam Pencegahan Kecanduan Game Online Pada Siswa - Yuniar, Fira; Irfan, Muhammad; Mulyadin, Mulyadin (Fitrah, 2024)
Online gaming addiction among elementary school students has become a problem that affects their academic performance and discipline. This study aims to analyze the application of a collaborative intervention model between parents and teachers in preventing online gaming addiction among students at MIS Yasim Mawu-Bima. This study uses a qualitative approach with a case study design. The research subjects consisted of 10 students identified as showing symptoms of addiction, with supporting informants including the principal, teachers, and parents. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that structured collaboration through routine communication, restrictions on gadget use, counseling, joint supervision, and the use of WhatsApp groups effectively reduced the duration of gaming and increased students' responsibility for learning. Supporting factors included the commitment of parents and teachers and intensive communication, while inhibiting factors included parents' time constraints and low digital literacy. It was concluded that the parent-teacher collaborative intervention model is a relevant preventive strategy in reducing online game addiction among elementary school students.